THE INFLUENCE OF GIVING LEADERSHIP STYLE INCENTIVES AND WORK ENVIRONMENT ON THE WORK SPIRIT OF GENERATION Z EMPLOYEES IN SUBANG DISTRICT - Asri Widianingsih; Rina Dwiarti (Sean Institute, 2023)
Human resources are very influential on the economic development of a local or global company. That is why the provision of incentives, leadership style and work environment is an important part of human resource management, so that it can affect the morale of an employee which can support the company's achievements. The purpose of this study was to find out whether the provision of incentives, leadership style and work environment affect employee morale. This type of research used is quantitative research. This research was conducted on generation Z employees in Subang Regency. The research population is 100 Generation Z employees. The probability sampling method is simple random sampling. The results showed that the provision of incentives, leadership style and work environment had a significant positive effect on employee morale.